Sosialisasi Berbagai Peluang Usaha UMKM Dan Ekonomi Kreatif Pasca COVID-19 Di Desa Suci Kecamatan Karangpawitan Kabupaten Garut - Eliya Fatma Harahap (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
The implementation of Community Service is intended to provide socialization to the community about the existence of various MSME business opportunities and the creative economy during the time when the Covid-19 pandemic ended. The main target of this Community Service is the community or residents in Suci Village, Karangpawitan District, especially those affected by the ongoing Covid-19 pandemic. This PKM activity was carried out to share knowledge about various business opportunities in times of crisis, as well as to distribute information related to the socialization that was carried out. With the socialization program for various MSME business opportunities and the creative economy post-Covid-19, it is hoped that the target community for this PKM activity will be aware of various MSME business opportunities and the creative economy to be used as motivation in an effort to take advantage of all available opportunities. Campus academics are also expected to become a source of knowledge, liaison or interface with MSME stakeholders and become a center of excellence in MSME business development through the creative economy.